On the origin of Czech farkas and cabraka - Tolgyesi, Tamas (Bohemica Olomucensia, 2018)
Hungarian farkas [fɒrkɒʃ] 'crupper' was most likely an adjective which was created from the noun fark 'tail' with the suffix -as. Instead of the expression farkas szij 'strap under the (horse's) tail' was simply used farkas, which in the course of time was substantivised and borrowed into the Czech language.Czech cabraka, Slovak cabraka, cabrak, Polish czaprag 'saddlecloth' most probably come via Hungarian csaprag [ʧaːpraːg] from Turkish caprak. German Schabracke, Czech sabrak, sabraka, Slovak sabrak, sabraka, Polish szabrak, szabraka and Slovenian sabraka forms were borrowed via Hungarian sabrak [ʃɒbraːk] from Turkish saprak.
Keywords: Czech; Hungarian; borrowing; crupper; saddlecloth